2020
DOI: 10.1088/1361-6455/ab8715
|View full text |Cite
|
Sign up to set email alerts
|

Measuring out-of-time-ordered correlation functions with a single impurity qubit in a bosonic Josephson junction

Abstract: We calculate the out-of-time-ordered correlation function (OTOC) of a single impurity qubit coupled to fully a connected many-particle system such as a bosonic Josephson junction or spins with long-range interactions. In these systems the qubit OTOC can be used to detect both ground state and excited state quantum phase transitions (QPTs), making it a robust order parameter that is considerably more sensitive than the standard one-body correlation function. Finite size scaling exponents for an N body system ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Here, the polaronic behavior should strongly depend on the involved interactions and an intriguing prospect would be to engineer specific entangled polaron states in certain interaction regimes with an additional knob provided by the interspecies mass-imbalance. Moreover, we should also emphasize that these hybridized systems are of further interest due to the fact that one subsystem (impurity) lies in the deep quantum regime while the other one (medium) can be potentially described semi-classically [72][73][74][75][76][77]. For instance, it has been demonstrated that following an impurity-bath interaction quench leads to chaotic signatures in the dynamics of the bath accompanied by significant coherence losses [77].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the polaronic behavior should strongly depend on the involved interactions and an intriguing prospect would be to engineer specific entangled polaron states in certain interaction regimes with an additional knob provided by the interspecies mass-imbalance. Moreover, we should also emphasize that these hybridized systems are of further interest due to the fact that one subsystem (impurity) lies in the deep quantum regime while the other one (medium) can be potentially described semi-classically [72][73][74][75][76][77]. For instance, it has been demonstrated that following an impurity-bath interaction quench leads to chaotic signatures in the dynamics of the bath accompanied by significant coherence losses [77].…”
Section: Introductionmentioning
confidence: 99%
“…The Out-of-Time-Order correlators (OTOC) are known to provide a diagnostic for scrambling which precedes thermalization in a typical non-integrable quantum many-body system [51][52][53][54][55][56]. Examples of such systems include large N spin and bosonic models [57][58][59]. For such models, which have well-understood semi-classical limits, the early time behavior of the OTOC constitutes an exponential growth and can be written as…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we investigate a binary ultracold atomic mixture made of a single impurity and a noninteracting many-body bosonic ensemble that are confined within a 1D DW potential. Unlike most of the previous studies where the focuses are put on the weak-interacting regime, rendering the impurity being restricted into the lowest two modes of the DW potential [51][52][53][54][55][56], our discussions are not restricted to such a scenario. Specifically, we study the onset of the chaos for the majority bosonic species due to the presence of the impurity and put particular emphasis on the its dynamical response upon a sudden quench of the impurity-Bose interaction strength.…”
Section: Introductionmentioning
confidence: 99%